2009
DOI: 10.1111/j.1540-8159.2008.02196.x
|View full text |Cite
|
Sign up to set email alerts
|

Does ICD Indication Affect Quality of Life and Levels of Distress?

Abstract: The implantable cardioverter defibrillator (ICD) is the treatment of choice for life-threatening arrhythmias, with ICD indications having recently been extended to include primary prophylaxis. Despite the medical benefits of the ICD, there is an ongoing debate as to the impact of the ICD on patients' lives, particularly whether primary prophylaxis implantation may impact adversely on patient-centered outcomes such as quality of life (QoL) and distress. We examined the evidence for a role of ICD indication on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 21 publications
(51 reference statements)
5
52
1
11
Order By: Relevance
“…Although Pedersen and colleagues 37 concluded that there is currently no evidence that adult patients who receive ICDs for primary prevention of SCA have poorer QOL or greater distress than those receiving ICDs for secondary prevention, this may not be the case in pediatric ICD recipients. The issue is prominent for those pediatric/ adolescent patients with anatomically normal hearts and genetically determined diseases that put them at risk for SCA, particularly when it comes to sports participation.…”
Section: Postimplantation Early Recovery and Adjustmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Although Pedersen and colleagues 37 concluded that there is currently no evidence that adult patients who receive ICDs for primary prevention of SCA have poorer QOL or greater distress than those receiving ICDs for secondary prevention, this may not be the case in pediatric ICD recipients. The issue is prominent for those pediatric/ adolescent patients with anatomically normal hearts and genetically determined diseases that put them at risk for SCA, particularly when it comes to sports participation.…”
Section: Postimplantation Early Recovery and Adjustmentmentioning
confidence: 97%
“…2,3,35,36 Equivalent QOL outcomes generally have been demonstrated between primary and secondary prevention indications. 37,38 QOL outcomes remain an area of intense research, because refinement of measures including generic and disease-specific parameters, evaluation of clinically and statistically significant differences, survivor and missing data sample biases, and evolving sophistication of the technology may change our understanding of the QOL outcomes and patient experiences with ICDs over time.…”
Section: Qol After An Icdmentioning
confidence: 99%
“…Nearly 30% of patients develop clinically significant levels of depression and/or anxiety [5], and 21% reported posttraumatic stress disorder (PTSD) [6]. ICD shocks, and more importantly, simply the fear of imminent shocks have a further detrimental effect on the patient's QoL [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although undoubtedly valuable to decrease arrhythmic and all-cause mortality, ICDs represent a suppressive therapy and do not prevent recurrences of ventricular arrhythmias. Repeated shocks for the termination of multiple episodes of ventricular arrhythmias may affect both quality of life [5] and survival [6] , while inappropriate shocks for supraventricular arrhythmias represent a clinical problem, especially in patients receiving an ICD for primary prevention [7] . In this scenario, a single therapy might not be the best option for every patient.…”
Section: Introductionmentioning
confidence: 99%